The association between general practitioner regularity of care and 'high use' hospitalisation - Moorin, Rachael; Youens, David; Preen, D.B.; Wright, Cameron (2020)
Background: In Australia, as in many high income countries, there has been a movement to improve out-of-hospital care. If primary care improvements can yield appropriately lower hospital use, this would improve productive efficiency. This is especially important among 'high cost users', a small group of patients accounting for disproportionately high hospitalisation costs. This study aimed to assess the association between regularity of general practitioner (GP) care and 'high use' hospitalisation.